Analyzing the impact of e-commerce strategies in building better relationships between the investors and consultancy firms during this pandemic - Ahmed, Syed Hasan (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.